Anthropogenically-induced range expansion as an invasion front in native species: An example in North American flying squirrels - Diggins, Corinne A. (Frontiers in Ecology and Evolution, 2023)
Biological invasions are typically framed as non-native species impacting the populations of native species or ecosystems. However, in a changing world, taxonomically similar native species that were previously parapatric or allopatric may become increasingly sympatric over short time periods (<100 years). In the context of climate change in the Northern Hemisphere, this may have a negative impact on northern species whose ranges are being invaded by southern species. To highlight factors that may influence invasion fronts in native species, I will use two species of North American flying squirrels, small-bodied nocturnal arboreal Sciurids, as an example. I will discuss what factors may enable or limit the expansion of southern flying squirrels (SFS; Glaucomys fuscus) into northern flying squirrel (NFS; Glaucomys sabrinus) habitat and potential impacts that anthropogenically-induced factors have on range shift dynamics. The range expansion of SFS may impact NFS via resource competition, hybridization, and parasite-mediation. Factors potentially enabling the expansion of SFS into NFS habitat include anthropogenic habitat disturbance and climate change, wherein historical land-use (i.e., logging) alters forest composition increasing habitat suitability for SFS and a warming climate allows SFS to expanded their ranges northward into colder regions. Shifts in forest species composition from historical logging may interact with a warming climate to enable SFS to quickly expand their range. Factors limiting SFS expansion include thermoregulation limitations and absence of potential food and denning resources. The factors influencing the dynamics between these two species may be applicable to the shifting ranges of other taxonomically and functionally similar native species in the context of a rapidly changing world in the Anthropocene.